Experimental Study on Warm Permafrost Dynamic Characteristics under Cyclic Loading in the Cold Region - Liwei Song; Junfang Liu; Yan Jin; Chi Li; Songbao Cai (Advances in Civil Engineering)
With the rapid development of infrastructure construction, some places have to face the problem of highway foundation disease, especially for the highway built on warm permafrost in cold region. In order to analyze the influence of confining pressure and vehicle load to the warm permafrost, the dynamic triaxial tests were conducted on the frozen soil extracted from highway in Yakeshi City. While the load frequency is 6 Hz and the test temperature is −1.5°C, we changed the confining pressure and axial stress amplitude, respectively, and then gained the deviator stress-strain curves. The test results show that the shape of deviator stress-strain curve is related to the deviator stress amplitude. When σ3=25 kPa and σ1−σ3|max=75 kPa, the hysteretic loops approximately appear rectangular and the dynamic modulus increases with loading time increasing for the compression effect. The specimen did not fail when the test stopped, and its hysteretic loop is stable. When σ3=20 kPa and σ1−σ3|max=100 kPa, the hysteretic loops become smoother and appear oval. The test stopped while the axial strain reached 5% after loading 1279 times, and the dynamic modulus decreases with loading time increasing. When σ3=30 kPa and σ1−σ3|max=115 kPa, the test stopped just after the 154th loop, and the hysteretic loop area linearly decreased with increasing loading time. The research conclusions in this article have numerous reference values for the highway design, construction, and operation built on the warm permafrost.